Recruiting and Retaining for IT SME : An Employee Perspective - Kanagalingam, Sivaruban (2013)
Businesses these days are competing at a breakneck speed. Having that competitive advantage can allow a company to stay a step ahead of its competitors. For small and medium enterprise (SME) owners, specifically those in the information technology (IT) sector, acquiring these employees may not be that easy. They would have to compete with not only others of their kind but large IT based organization that can offer a multitude of benefits. Therefore, it is crucial that IT SME owners discover factors that can attract potential candidates to join their company. Additionally, these owners would also need to identify factors that can assist them in retaining those valuable employees. The purpose of this paper is to explore three objectives. The first is to discover factors that can attract candidates to join an IT SME. Secondly, to identify factors that can assist in retaining those employees and finally,uncovering factors that can cause an employee to leave. The context of this study was conducted within the IT SME industry in Malaysia. Twenty respondents from six different IT SMEs participated in this qualitative study.The findings of this paper do suggest that there are four factors that IT SME owners could focus on. They are “financial rewards”, “job content”, ”company culture” and “career opportunity”. Each of these factors has yielded interesting outcomes however the preferences and impact of these factors varies between different demographics. Therefore it could be proposed that owners could focus on these factors in order to assist them in attracting and retaining these employees however they would need to first identify the demographic that they would like to target before applying these factors. Finally this paper also proposes a simple framework that owners could possibly use to kick-start the attraction of potential candidates and retention of employees within their company.